Geological structures affecting the marble mining in the Apuan Alps (Northern Apennines) - Carmignani, Luigi; Conti, Paolo; Massa, Giovanni; Pieruccioni, Diego; Xhixha, Elona; Khyabani, Fahimeh Ryazi (Italian journal of engineering geology and environment, 2017)
<span data-sheets-value=""1":2,"2":"The still ongoing studies on the geology of the Apuan Alps show the presence of a deformational event which is developed in the late-metamorphic to post-metamorphic conditions (D3), that has occurred on the previous structures and has created the low-angle shear zones and high-angle faults, associated with both right hand and left hand complicated movement systems. These shear zones represent a new element in the geological landscape of the Apuan Alps, and our knowledge about them is deducted from the information obtained from the traditional geological-structural surveys and photo-interpretation of data derived from aerial LIDAR and optical proximal sensing. The effects of brittle/ductile to ductile deformation which characterizes the Apuan Metamorphic Complex, has established the development of shear zones consisting the mylonitic marbles, such as the specific types of Bianco, Bardiglio, Nuvolato and Arabescato marbles, which are distinguished by their excellent physical and mechanical characteristics, as well as having high commercial and aesthetic value. These particular structures and their three-dimensional architecture affect the geometry of the deposits of ornamental stones and as the consequence, also on the planning of medium and long-term mining activities."" data-sheets-userformat=""2":13057,"3":"1":0,"11":0,"12":0,"15":"Arial","16":10">The still ongoing studies on the geology of the Apuan Alps show the presence of a deformational event which is developed in the late-metamorphic to post-metamorphic conditions (D3), that has occurred on the previous structures and has created the low-angle shear zones and high-angle faults, associated with both right hand and left hand complicated movement systems. These shear zones represent a new element in the geological landscape of the Apuan Alps, and our knowledge about them is deducted from the information obtained from the traditional geological-structural surveys and photo-interpretation of data derived from aerial LIDAR and optical proximal sensing. The effects of brittle/ductile to ductile deformation which characterizes the Apuan Metamorphic Complex, has established the development of shear zones consisting the mylonitic marbles, such as the specific types of Bianco, Bardiglio, Nuvolato and Arabescato marbles, which are distinguished by their excellent physical and mechanical characteristics, as well as having high commercial and aesthetic value. These particular structures and their three-dimensional architecture affect the geometry of the deposits of ornamental stones and as the consequence, also on the planning of medium and long-term mining activities.